Precision lung resections as an alternative technology for the surgical stage of tuberculoma treatment - I. A. Dyachkov; I. Ya. Motus; A. V. Bazhenov; I. D. Medvinskiy; S. N. Skornyakov; R. B. Berdnikov (Туберкулез и болезни лёгких)
.